Gestando potes e pessoas : a cerâmica como processo de aprendizagem do sensível e concreto - Lilian Panachuk de Sá (2021)
In this research I seek to reflect on the Tupiguarani archaeological ceramics as an artifact that materializes learning relationships between generations of each community of practice. This relational network includes how to deal with and understand the phenomena, substances and things that are entangled in pottery manufacturing. In this case, the pottery includes both the process of making and the product. Making pottery comprises a lot of work and commitment, different knowledge about a multitude of uses and protocols, narratives that build and update intergenerational memory, specific techniques, rules of action and impediments. In order to debate this theme, I used a wide repertoire of narratives in search of the place of pottery and learning in communities that speak Tupi-Guarani, through historical, linguistic and ethnographic information. This analogical argument enables to situate pottery as an artifact that connects people through the long learning process, through narratives that awaken memory and create links between generations. This perception was useful to think about archaeological ceramics as materialization of these relationships, outlining a research that triggers learning to think about academic practice. Archaeological experimentation appears here as a strategy to include the producing body in the research, to think through the body. This scenario brought some color to think about the Tupiguarani archaeological ceramics. This research also want to emphasise, through the Tupi pottery, the history of women producing artifacts, stories and knowledge, who actively build life in their communities of practice. The ceramic learning process is long, involves humanities and materialities linked to the way of making ceramics and being a pottery artist in each community of practice, in a construction throughout life. This path is marked on the pottery pieces through technical gestures that are related to the result of practice and learning in a given community, it is a result of a diversity of people in its life cycle, it is a collective construction.